The Influence of Work Experience, Education Level, and Work Discipline On Employee Work Productivity at The Business Division of Perumda BPR Bank Sumedang - Rita Gustina Gustina; Nugraha Saefudin (International Journal of Science and Environment (IJSE), 2026)
This study aims to determine the influence of work experience, education level and employee work productivity on employee work productivity in the business division of Perumda BPR Bank Sumedang both partially and simultaneously. The type of research used in this study is a type of quantitative research with descriptive research objectives. The collection technique in this study uses questionnaires, interviews, documentation, and observations. The sample in this study used a census method with 118 respondents. The method used was quantitative descriptive verification through a questionnaire to 118 employees in the business division, analyzed by multiple linear regression using SPSS 27. The results of the study show that work experience has a significant positive effect on employee work productivity, education level has a positive and significant effect on employee work productivity, and work discipline has a positive and significant effect on employee work productivity.